Three important roles and chemical properties of glomalin-related soil protein - Son, Yejin; Martínez, Carmen Enid; Kao-Kniffin, Jenny (Frontiers in Soil Science, 2024)
The consequences of climate change urgently demand the reduction of atmospheric carbon, including by sequestering carbon in soil. The glomalin-related soil proteins (GRSP) of arbuscular mycorrhizal fungi (AMF) are renowned for their soil aggregation and carbon sequestration properties. With their considerable binding abilities, GRSP can also adsorb various cations and sequester heavy metals in soil, thereby assisting in soil fertilization and remediation efforts. However, despite its benefits for soil health and climate change, the mechanisms underlying these traits in the context of soil chemistry remain unexplored. In this review, we focus on three crucial roles of GRSP—long-term carbon sequestration, soil aggregation, and soil remediation and fertility—in the context of the chemical characteristics elucidated by previous research, namely hydrophobicity, amid group glycosylation (N-glycosylation), and metal adsorption. Based on the proposed chemical mechanisms, the current review also offers insight into soil factors that may influence the persistence of GRSP. We conclude by proposing a working model for GRSP, aiming to establish a conceptual platform for future research to examine GRSP in terms of their known or novel chemical and biochemical reactions, thereby improving our understanding of this important group of soil proteins.